THE PROBLEM OF HUMAN PERSONALITY FORMATION IN THE WORKS OF UKRAINIAN THINKERS OF THE SECOND HALF OF THE XVIII CENTURY (Pedagogy of Higher and Secondary Education, 2007)
1п clause the problem of formation of the moral person through éducation and éducation as achievement, necessary a condition, of happy life is considered.